2020
DOI: 10.1002/jmv.25802
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of an acute severe pneumonia patient with COVID‐19: Case report

Abstract: To the Editor, COVID-19 outbreak occurred globally and continues to grow. 1 COVID-19 is highly infectious and has incubation period of 0 to 24 days. 2,3 Moreover, asymptomatic patients can be contagious, 4 which indicates the importance of COVID-19 confirmation. The current diagnostic methods include rRT-PCR, genetic sequencing, and serum antibody detection. 2 rRT-PCR is the most commonly used method and can be used at early course. However, the rRT-PCR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Interestingly some of the data suggest that NPS tests may occasionally be negative when the corresponding saliva test gives a positive result. Azzi et al reported that two patients showed positive saliva tests while their NPS tests were negative ( 14 ), and a case report showed that in seven sample pairs from one individual, the NPS tests were all negative while the saliva tests were positive on each occasion ( 19 ). In a sample-based study of 38 patients, Wyllie et al ( 21 ) detected SARS-CoV-2 in saliva but not NPS specimens from eight patients (21%), while the virus was detected in NPS but not saliva in only 3 matched samples (8%).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly some of the data suggest that NPS tests may occasionally be negative when the corresponding saliva test gives a positive result. Azzi et al reported that two patients showed positive saliva tests while their NPS tests were negative ( 14 ), and a case report showed that in seven sample pairs from one individual, the NPS tests were all negative while the saliva tests were positive on each occasion ( 19 ). In a sample-based study of 38 patients, Wyllie et al ( 21 ) detected SARS-CoV-2 in saliva but not NPS specimens from eight patients (21%), while the virus was detected in NPS but not saliva in only 3 matched samples (8%).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 is the seventh and most novel human coronavirus. It emerged as a highly pathogenic species in December 2019 in Wuhan City, China and has since quickly spread to all continents except Antartica [5]. As of the time of this writing, the number of confirmed cases is more than one milion with thousands of deaths (https://www.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 TCM was found to be effective when used along with Western medicine but cannot be used as a single modality for treatment. 4,16,17 Convalescent plasma therapy 8,19 , Intravenous…”
Section: Resultsmentioning
confidence: 99%
“…Amidst COVID-19 outbreak traditional Chinese medicine was used in conjunction with western medicines like antivirals, antibiotics, oxygen therapy, interferon, and methylprednisolone. 4,16,17 Patients receiving a combination of Chinese medicine and Western medicine showed significant improvement. In a clinical trial of 562 patients, both groups showed a lowering of fever but the group receiving a combination of Chinese and Western medicine showed a smoother decrease in body temperature to normal as compared to fluctuating fever in the group receiving only western medicine.…”
mentioning
confidence: 99%